Comparison of Sinus Tarsi and Extensile Lateral Approach in Intra-articular Calcaneus Fractures - Necip Güven; Abbas Tokyay; Şehmuz Kaya; Tülin Türközü; Fatih Güzel; Sezai Özkan (Genel Tıp Dergisi)
Objective: In this study, we aimed to compare the clinical and radiological results of the extensile lateral (EL) approach and sinus tarsi (ST) approach in calcaneal fracture surgery. Materyal-Metod: A total of 40 patients with Sanders II-III calcaneal fractures, including 22 patients in the EL group and 18 patients in the ST group, were included in this retrospective study. In the radiological evaluation, changes in the calcaneus Bohler and Gissane angle, length, width, and height were measured during the preoperative and postoperative period. Clinically, American Orthopedic Foot and Ankle Society (AOFAS) and the visual analog scale (VAS) were evaluated. In addition, postoperative complications were also evaluated. Results: In terms of demographic data, the results of both groups were similar. Both the length of hospital stay and the time to surgery were shorter in the ST group (p=0.019, p=0.02, respectively). There was no significant difference between the groups regarding radiological, clinical AOFAS and VAS scores. 13.6% superficial infection was seen in the EL group, and no wound problems were encountered in the ST group (p=0.102). The rate of sural nerve injury was 36.4% in the EL group and 5.6% in the ST group (p =0.003). Conclusion: Both approaches clinical and radiological outcomes were similar. However, the advantages of the ST approach were shorter hospital stays, lower rate wound infections, and sural nerve injury problems.